A Phenomenological Study of Self-Regulation Among Employees in Deputy Department Head Positions Who Exhibit Turnover Intentions - Suryadi Suryadi; Yudistira Fauzi Indrawan (Eduvest - Journal of Universal Studies, 2026)
This study aims to determine self-regulation in employees holding deputy department heads who have intentions to quit their jobs. Self-regulation is an individual's ability to control their thoughts, feelings, and behavior through internal processes, so they can achieve desired goals. Meanwhile, intention to quit is a psychological concept that describes an employee's intention to leave their job voluntarily. This study used a qualitative method with a phenomenological approach. The participants were two individuals who had worked for 10-25 years. The research location was Bekasi City. Data analysis used interview, observation, and documentation techniques. The analysis results for both respondents showed different factors causing turnover intention. Respondent 1 had a significant influence on workload, while respondent 2 was more influenced by career path. Self-regulation aspects included job satisfaction, organizational commitment, work stress, self-development, and perceptions of alternatives. Respondent 1's most prominent aspect was workload. Respondent 2's most prominent aspect was self-development or career path in influencing turnover intention. Both respondents underwent several self-regulation processes, including self-observation, judgment, and self-response. Based on these analysis results, it can be concluded that both respondents were able to self-regulate.